2005
DOI: 10.1002/chem.200401209
|View full text |Cite
|
Sign up to set email alerts
|

Borate‐Catalyzed Reactions of Hydrogen Peroxide: Kinetics and Mechanism of the Oxidation of Organic Sulfides by Peroxoborates

Abstract: The kinetics of the oxidation of substituted phenyl methyl sulfides by hydrogen peroxide in borate/boric acid buffers were investigated as a function of pH, total peroxide concentration, and total boron concentration. Second-order rate constants at 25 degrees C for the reaction of methyl 4-nitrophenyl sulfide and H(2)O(2), monoperoxoborate, HOOB(OH)(3) (-), or diperoxoborate, (HOO)(2)B(OH)(2) (-), are 8.29 x 10(-5), 1.51 x 10(-2) and 1.06 x 10(-2) M(-1) s(-1), respectively. Peroxoboric acid, HOOB(OH)(2), is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…Insofar as the oxidation of organic sulfides by peroxoborate is concerned, the reactions generally proceed in a manner similar to other peroxobased oxidants, for instance, by development of a positive charge on the sulfur atom in the transition state with the sulfide behaving as nucleophile, yet there is a succinct difference. The difference lies in mono and diperoxborates having the transition state earlier along the reaction coordinate [2] with relatively less positive charge being developed on the sulfur atom. This in turn emphasizes that proton transfer would play a significant role in the peroxoborate oxidation of organic sulfides.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Insofar as the oxidation of organic sulfides by peroxoborate is concerned, the reactions generally proceed in a manner similar to other peroxobased oxidants, for instance, by development of a positive charge on the sulfur atom in the transition state with the sulfide behaving as nucleophile, yet there is a succinct difference. The difference lies in mono and diperoxborates having the transition state earlier along the reaction coordinate [2] with relatively less positive charge being developed on the sulfur atom. This in turn emphasizes that proton transfer would play a significant role in the peroxoborate oxidation of organic sulfides.…”
Section: Introductionmentioning
confidence: 97%
“…The discovery of hydrogen carbonate catalyzed oxidation of organic sulfides [1] through peroxocarbonate (HCO 4 -) and the subsequent seminal contributions of Davies and coworkers [2] showing that borate is a better catalyst than HCO 4 -with rapidly formed peroxoborates, HOOB(OH) 3 -and (HOO) 2 B(OH) 2 -, being more reactive than HCO 4 -, and extending the pH functional range to the 8-12 region are very important developments in the realm of oxidation chemistry of organic sulfur. The examples to bear with this contention include oxidants like H 2 O 2 , [3] periodate, [4] peracids, [5] permonosulfate, [6] and peroxymonocarbonate.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, we have recently shown that the electrophilic oxidation of organic sulfides by hydrogen peroxide is catalyzed in borate/boric acid buffers by the formation of peroxoborates. [1] Relevant equilibria are given in Equations (1) and (2), where K BOOH is the formation constant of monoperoxoborate, [2] and K BOH is the formation constant of borate (i.e. the acid dissociation constant of boric acid).…”
Section: Introductionmentioning
confidence: 99%
“…For runs above pH 9.5, small aliquots were removed from the reaction vessel at measured time intervals and analysed for total peroxide using the titanium IV method. [1] Values of k obs were determined using Equation (6) with the value of l for the reaction vessel that was determined as described in the next paragraph. For runs below pH 9.5, where the peroxide absorbs weakly at 254 nm, the absorbance of the reaction solution at 220 nm was measured directly, and k obs values determined using Equation (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation